Effect of Jingui Shenqi Pill on the Differential Proteins in Femoral Cortical Bone of Kidney-yang Deficiency Rats Model - Naixi ZHENG; Zhengxuan ZHAN; Yingjie ZHANG; Xu WANG; Ziyi ZHANG; Youxin SU (康复学报)
Objective:To study on the mechanism of Jingui Shenqi pill treatment of kidney-yang deficiency from the angle of differential protein.Methods:We established the model of kidney-yang deficiency rats, set up the normal group, the kidney-yang deficiency group and the traditional Chinese medicine group (Jingui Shenqi pill group). We used two-dimensional electrophoresis (2-DE) to show the proteomic maps of femoral cortical bone, compared the differential protein spots between the groups, analyzed and identified them by mass spectrometry.Results:There were 480 discernible proteins points in each 2-DE gel map. Compared with the normal group, the kidney-yang deficiency group had 16 differentially expressed proteins. After treatment with Jingui Shenqi pill, in the kidney-yang deficiency model rats, the up-regulated expression of Apoa1, Hspd1 and the down-regulated expression of Tpm3, Arhgdib, Colla1 and Sri were back-adjusted.Conclusion:Jingui Shenqi pill in the treatment of kidney-yang deficiency is related to adjust the protein expression of femoral cortical bone in rats. Those proteins involve Apoa1, Hspd1, Tpm3, Arhgdib, Colla1 and Sri.